Assessment of the Effectiveness of Cognitive- Existence Realistic Group Therapy on Anxiety and Depression in Patients with Breast Cancer - Hamidreza Arman; Noshirvan Khezri Moghadam (Islamic Azad University, 2016)
Introduction: Cancer is one of the most important health problems around the world today, and its prevalence is higher in industrialized countries. The purpose of this study was to evaluate the efficacy of cognitive-existence realistic group therapy on anxiety and depression in breast cancer patients. Methods: The research design was of experimental type, having pre-test and post-test with two groups of experiments and control. The statistical population of this study consisted of women suffering from breast cancer, aging 18 to 60 years old in spring 2016 who referred to Afzali Hospital in Kerman to use therapeutic facilities (chemotherapy and radiotherapy). The sample group included 30 patients referring to the medical centers of Kerman who announced their readiness to attend the group therapy session after the introduction of the program. Sample groups consisted of 2 groups of 15 cancer patients (15 patients in the control group and 15 in the experimental group). Both groups responded to Beck Depression Inventory (1961) and Beck Anxiety Inventory (1988) before and after the experiment. Data were analyzed using statistical methods such as distribution table, frequency charts, mean and standard deviation, and covariance analysis (p≤0.05). Results: The results showed that cognitive-ontological group therapy had an effect on the anxiety of patients with cancer at a significance level of (p <0.01). Also, cognitive-ontological group therapy had a significant effect on depression in patients with cancer at a significant level of (p <0.01). Conclusion: Cognitive-existence realistic group therapy can reduce depression and anxiety in patients with breast cancer.